2021
DOI: 10.1029/2020jd033516
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Accuracy and Efficiency of Atmospheric Models in the Northern Adriatic During Severe Bora Events

Abstract: In process‐oriented studies, accurate representation of severe bora rotor dynamics in the northern Adriatic is known to require the use of model resolutions of the order of 100 m. In regional climate studies, computation time and numerical cost are, however, minimized with resolutions of the order of 10 km. The latter is not accurate enough to drive the coastal dense water formation and the long‐term Adriatic‐Ionian thermohaline circulation resulting from these events. This work leverages the capacity of kilom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 117 publications
2
29
0
Order By: Relevance
“…computational resources and running time)depending of the temporal and spatial scales of the studied processesremains one of the major issues of the climate modelling community. For example, (1) the RCMs of the Med-CORDEX community have already been proven to largely underestimate the dense water budget of the Adriatic Sea (Dunić et al, 2019), while (2) the recently developed MEDSEA ocean re-analysis at approximately 4-5 km (Escudier et al, 2020) is forced by the ERA5 atmospheric re-analysis known to underestimate the extreme bora events (Denamiel et al, 2021a). To properly capture the Adriatic thermohaline circulation triggered by the dense water formation in the northern Adriatic Sea, the reliability of MEDSEA in the Adriatic Sea thus largely depends on the data assimilation and not the physics.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…computational resources and running time)depending of the temporal and spatial scales of the studied processesremains one of the major issues of the climate modelling community. For example, (1) the RCMs of the Med-CORDEX community have already been proven to largely underestimate the dense water budget of the Adriatic Sea (Dunić et al, 2019), while (2) the recently developed MEDSEA ocean re-analysis at approximately 4-5 km (Escudier et al, 2020) is forced by the ERA5 atmospheric re-analysis known to underestimate the extreme bora events (Denamiel et al, 2021a). To properly capture the Adriatic thermohaline circulation triggered by the dense water formation in the northern Adriatic Sea, the reliability of MEDSEA in the Adriatic Sea thus largely depends on the data assimilation and not the physics.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Therefore, to quantify the impacts of climate change in the Adriatic, it is crucial to obtain an adequate representation at climate scales of the atmosphere-ocean interactions during extreme events which are, for example, driving the formation of dense water within the basin. Atmospheric RCMs generally fail to provide such a representation, especially in the northern Adriatic where they cannot be used to study the extreme bora dynamics (Denamiel et al, 2020b(Denamiel et al, , 2021a. Additionally, it has also been recently demonstrated that the latest higher resolution ECMWF reanalysis datasetthe ERA5 product (Hersbach et al, 2018), cannot be used either as a reference for climate model evaluation nor as a forcing for ocean models during bora events in the northern Adriatic as it also strongly underestimates the extreme bora speeds (Denamiel et al, 2021a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The high-resolution atmosphere-ocean Adriatic Sea and Coast (AdriSC) climate model (up to 3 km in the atmosphere and 1 km in the ocean) was thus implemented, and a 31-year-long evaluation simulation was performed for the 1987-2017 period. In this work, the performance of the AdriSC ocean coastal model is evaluated, while the skill assessment of the AdriSC atmospheric kilometre-scale model is done in a separate study (Denamiel et al, 2021b). In general, a proper evaluation of a high-resolution climate model is not a trivial task and most often the biggest challenge turns out to be the availability, incompleteness, and scarcity of observational data, as well as the imperfections of the observing systems, which set further limits on the evaluation process (Horak et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Rinke etal. 2011;Nikulin et al, 2012;da Rocha et al, 2014;Huang et al, 2015;Ruti et al, 2016;Zou and Zhou, 2017;Di Virgilio et al, 2019). Specifically, in the Mediterranean Sea, several RCMs have been developed within the Med-CORDEX initiative (e.g.…”
Section: Introductionmentioning
confidence: 99%